Construction player’s perception of training approach using serious game–A pilot study - Mohd., Norhazren Izatie (Penerbit UTM Press, 2015)
Construction workers are always exposed to numerous occupational hazards of different kinds and levels of complexity in every project they engage in. Therefore, there is a need for training modules which can provide the knowledge to construction workers to acquire the skills necessary for occupational and environmental safety on site. However, current safety training still lacks hands-on approaches and it is theory-oriented. This is due to the nature of the construction environment itself in which hands-on approaches are impossible to be applied for certain types of hazards. Training which is assisted by technology is an effective tool in improving learning for not just for children but also for adults. Currently, serious game has become a new approach in training and learning not limited to the field of education but this approach has been applied across disciplines and areas including military, mining, transportation, oil and gas and also the construction industry. Therefore, this paper sought to review construction workers’ perceptions toward serious game as a training tool. Fifty players at various levels from the construction industry participated in a pilot study. A set of questionnaire was distributed to the participants during an occupational safety and hazard (OSH) training course with the cooperation of OSH state agency in the southern region of Peninsular Malaysia and also online. Descriptive statistics were used to analyze data from the questionnaire. Preliminary findings of the pilot study indicated that construction workers had high expectation toward serious game in delivering hands-on training in safer environment. They also believed training module using serious game had the potential in creating affordable, interactive and entertaining training module for the industry. The study contributes to an understanding of occupational safety training needs in the construction industry for a safer, more affordable and interactive as well as entertaining approach.